2012
DOI: 10.4161/rna.22290
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of mouse selenoprotein P transcript variants differing in non-coding RNA

Abstract: Selenoprotein P (Sepp1), a glycoprotein rich in selenium, is thought to function in selenium transport throughout the body. The sepp1 gene locus potentially produces three alternative transcripts that differ only in their 5' untranslated regions (5'UTRs) and not in their protein coding regions, as indicated by transcript information in genomic databases. Here we investigated the distribution, relative expression, and biological significance of these transcript variants. We confirmed the expression of Sepp1 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…1, TUG1 is expressed in many tissues, including the brain. Studies have shown that brain-selective kinase2 phosphorylation of PCTAIRE1 negatively regulates glucose-stimulated insulin secretion in pancreatic beta cells [35]. As certain signals in the brain can affect beta cells or GSIS, the in vivo results for blood and insulin may be due to TUG1 knockdown in tissue other than the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…1, TUG1 is expressed in many tissues, including the brain. Studies have shown that brain-selective kinase2 phosphorylation of PCTAIRE1 negatively regulates glucose-stimulated insulin secretion in pancreatic beta cells [35]. As certain signals in the brain can affect beta cells or GSIS, the in vivo results for blood and insulin may be due to TUG1 knockdown in tissue other than the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In an early analysis of Sel P mRNA sequence, conserved regions were found that could potentially regulate SelP incorporation (134). The 5’ untranslated region (5‘UTR) of rat SelP was initially shown to be short (approximately 38 bases) and not very conserved, but a recent study has shown that human SelP exists as three alternative transcripts differing only in their 5‘UTR lengths (135). The smallest 5' UTR (approximately 76 bases) corresponds to the most abundant transcript and also has a target site for micro-RNA mir7 which may potentially play a role in SelP translation efficiency.…”
Section: Regulation Of Selenoprotein Synthesismentioning
confidence: 99%
“…The smallest 5' UTR (approximately 76 bases) corresponds to the most abundant transcript and also has a target site for micro-RNA mir7 which may potentially play a role in SelP translation efficiency. The 5‘UTR of the 3 transcripts were predicted to fold with varying secondary structure complexity and it was speculated that this variation could in turn alter rate and efficiency of SelP translation (135). …”
Section: Regulation Of Selenoprotein Synthesismentioning
confidence: 99%
“…MicroRNA-7 (miR-7) has been proven to play a substantial role in tumorigenesis and to progress by several signaling pathways in various tumors, but its functions in the context of HCC need further study and investigation. [11][12][13][14] The selected miR-7 was analyzed by miRcode database (available at http://www.mircode.org/?gene=sepp1&mirfam=miR-7%2F7ab&class=&cons=&trregion) and based on previous study of Dewing et al, 15 where selenoprotein P (SeP) was selected as miR-7 target pair. SeP was retrieved and confirmed as an associated gene with HCC from gene atlas database (available at http://genatlas.medecine.univ-paris5.…”
Section: Introductionmentioning
confidence: 99%